Difficulties of valuating the emotional side of students in secondary school during the physical and sport education session - Berbouche , Tarek; Fennouche , Nacir (sports creativity, 2025)
Our research aimed at shedding the light on the emotional side of secondary school students according to many different teachers' points of view and the nature of the obstacles that caused the neglection of this side which is extremely important in the student's personality and one of the main ultimate goals of the physical education and sports rather than the cognitive and the motor sense. The target population was many different teachers of physical education and sports in Biskra city where we have chosen a random sample which were 20 teachers from different schools in a specific area in Biskra. Then we have tried to draw out a coherent conclusion from the results of our research in order to make sure that the emotional side should be evaluated during the sport courses